The patient experience of a postpartum readmission for hypertension: a qualitative study - Radhika Viswanathan; Sarah E. Little; Louise Wilkins-Haug; Ellen W. Seely; Saba H. Berhie (BMC, 2024)
Abstract Background Hypertensive disorders of pregnancy (HDP) are the most common cause of postpartum readmission. Prior research led to clinical guidelines for postpartum management; however, the patient experience is often missing from this work. The objective of this study is to understand the perspective of patients readmitted for postpartum hypertension. Methods This was a qualitative study with data generated through semi-structured interviews. Patients readmitted with postpartum HDP at an urban academic medical center from February to December 2022 were approached and consented for an interview. The same researcher conducted all interviews and patient recruitment continued until thematic saturation was reached (n = 9). Two coders coded all interviews using Nvivo software with both deductive and inductive coding processes. Discrepancies were discussed and resolved with consensus among the two coders. Themes were identified through an initial a priori template of codes which were expanded upon using grounded theory, and researchers were reflexive in their thematic generation. Results Six themes were generated: every pregnancy is different, symptoms of preeclampsia are easily dismissed or minimized by both patient and providers, miscommunication regarding medical changes can increase the risk of readmissions, postpartum care coordination and readmission logistics at our hospital could be improved to facilitate caring for a newborn, postpartum care is often considered separately from the rest of pregnancy, and patient well-being improved when conversations acknowledged the struggles of readmission. Conclusions This qualitative research study revealed patient-identified gaps in care that may have led to readmission for hypertensive disorders of pregnancy. The specific recommendations that emerge from these themes include addressing barriers to blood pressure management prior to discharge, improving postpartum discharge follow-up, providing newborn care coordination, and improving counseling on the risk of postpartum preeclampsia during discharge. Incorporating these patient perspectives in hospital discharge policy can be helpful in creating patient-centered systems of care and may help reduce rates of readmission.